2016
DOI: 10.1080/09720529.2015.1085730
|View full text |Cite
|
Sign up to set email alerts
|

Survey and analysis of security issues on RSA algorithm for digital video data

Abstract: RSA is an encryption algorithm which is used for remote login session, credit card payment systems, transport layer security, secure socket layer, pretty good privacy and email security. Optimal asymmetric encryption padding is used in RSA to avoid chosen-ciphertext attack, coppersmith attack and chosen-plaintext attack. However, encryption in context of high definition video files shows repetitions of parts of ciphertext which can lead to frequency analysis attack. Key length and padding which are used in att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Based on a study by [29], it is reported that encryption may introduce a heavy calculation. However, studies [7], [30] have concluded that using hash function is appropriate to meet the requirement. In comparison with encryption cryptography, it has less computation regarding processing time and much lightweight.…”
Section: Dad-match Technique Proposal To Secure Ipv6 Dad Processmentioning
confidence: 99%
“…Based on a study by [29], it is reported that encryption may introduce a heavy calculation. However, studies [7], [30] have concluded that using hash function is appropriate to meet the requirement. In comparison with encryption cryptography, it has less computation regarding processing time and much lightweight.…”
Section: Dad-match Technique Proposal To Secure Ipv6 Dad Processmentioning
confidence: 99%
“…Because of the key-related operation in the RSA key generation algorithm, the key can be solved by analyzing the characteristics of the key generation algorithm. Final method is combined with the side-channel attack on the key generation algorithm for iterative bit-by-bit attack, the same successful reduction of the key search space [18,19,20,21].…”
Section: Side-channel Attack Based On Rsa Algorithmmentioning
confidence: 99%